Cytauxzoon felis in Domestic Cats: A Molecular Study Using Real-Time PCR in Semnan, Iran - Masoud Ebrahimi Toodarvari; Hesamedin Eskafian; Hamid Staji; Mahmood Ahmadi-hamedni (Iranian Journal of Parasitology, 2025)
Background: Cytauxzoon felis is a protozoan parasite transmitted by ticks and affects felids. Acute infection in domestic cats is characterized by symptoms such as lethargy, anorexia, fever, and anemia. Methods: The present study focuses on diagnosing and molecularly identifying C. felis using a real-time PCR method in cats from Semnan, Iran. During the winter and spring of 2024, two hundred cats were randomly selected from veterinary clinics in Semnan. Blood samples were collected from the cats for DNA extraction and molecular analysis. Samples were divided into 40 pooled of 5 samples, each consisting of a combination of 5 blood samples. Then, the genomic DNAs were extracted from blood specimens and screened by real-time PCR (RT-PCR) for the presence of C. felis infection by amplifying of ITS2 gene belonging to the Cytauxzoon genus. Results: The results indicated that 6 out of the 200 blood samples were infected (3%). Conclusion: This study was conducted for the first time in Semnan and shows that the prevalence of C. felis in cats is significant.